The influence of moral and ethical aspects on the organisation’s economic security - S. A. Antonov (Вестник университета)
The modern features of the moral and ethical values implementation in the individual’s and society’s economic life have been considered. The negative consequences of the moral norms current system in economic relations and the difficulties of taking into account the activity’s ethical aspects have been revealed. The economic life key problems of a part of modern society have been indicated, namely: “goals substitution by means” and “absolute norms loss”, which gradually turns the humanity’s life into an instinctive struggle of living organisms for the goods consumption. In conclusion, attention has been paid to the need to organise axiological studies of the Russian economic life and foreign countries in order to increase the economic security level of organisational and managerial solutions to the national economy problems.